IMPLEMENTASI PROGRAM KEAGAMAAN SEKOLAH BERASRAMA JENJANG SMA DI KOTA BANDA ACEH - Huwaida, Huwaida (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2023)
Boarding school is a form of educational institution that has its own advantages, one of which is in terms of religious coaching. This is because boarding school students have more opportunities to take part in religious activities organized by the school. There are high schools in Banda Aceh that run boarding school program or boarding program and implement religious programs inside. This research aims to reveal the implementation of religious programs in boarding schools and the obstacles faced in implementing religious programs in boarding schools at the high school level. Data collection was carried out through interviews and documentation. The results show that religious programs have been implemented in boarding schools at the high school level with a variety of activities and benefits for students. Barriers were also found in implementing religious programs related to student motivation, religious program mentors, student conditions, facilities and infrastructure as well as religious program learning.